Operation and Handling in Escort Tugboat Manoeuvres with the aid of Automatic Towing Winch Systems. (January 2015) - Carral Couce, Luis; Carral Couce, Juan Carlos; Fraguela Formoso, José Ángel
<x content-type="archive" xml:space="preserve">Abstract</x> An escort tugboat comes to the aid of a vessel when that vessel is navigating in confined waters and at a speed that is usually higher than six knots. In the escort manoeuvre, two systems come into play. One is the propulsion and steering of the vessel. The other involves the tug winch in terms of the tension it exerts and the length of towline released. In this way, the tug winch becomes a key piece of equipment. Along with the difficulties of carrying out the manoeuvre itself are the risks resulting from the operation of the winch. For this reason, automatic manoeuvring systems have been developed to facilitate this operation. They consist of information technology applications that help the skipper with manoeuvring the tug. At the same time, they make it possible to display and monitor the most important parameters of the towing winch. This study will describe a control system for the towline so that it can help carry out the towing manoeuvre with an escort tug. It indicates the control parameters for the manoeuvre, as well as the operational variables of the winch on which the system runs.